Cultivated Olive Diversification at Local and Regional Scales: Evidence From the Genetic Characterization of French Genetic Resources - Khadari, Bouchaib; El Bakkali, Ahmed; Essalouh, Laila; Tollon, Christine; Pinatel, Christian; Besnard, Guillaume (Frontiers in Plant Science, 2019)
Molecular characterization of crop genetic resources is a powerful approach to elucidate the origin of varieties and facilitate local cultivar management. Here we aimed to decipher the origin and diversification of French local olive germplasm. The 113 olive accessions of the ex situ collection of Porquerolles were characterized with 20 nuclear microsatellites plus their plastid haplotype. We then compared this collection to Mediterranean olive varieties from the Worldwide Olive Germplasm Bank of Marrakech, Morocco. High genetic diversity was observed within local French varieties, indicating a high admixture level, with an almost equal contribution from the three main Mediterranean gene pools. Nearly identical and closely related genotypes were observed among French and Italian/Spanish varieties. A high number of parent–offspring relationships were also detected among French varieties and between French and two Italian varieties (‘Frantoio’ and ‘Moraiolo’) and the Spanish variety (‘Gordal Sevillana’). Our investigations indicated that French olive germplasm resulted from the diffusion of material from multiple origins followed by diversification based on parentage relationships between varieties. We strongly suggest that farmers have been actively selecting olives based on local French varieties. French olive agroecosystems more affected by unexpected frosts than southernmost regions could also be seen as incubators and as a bridge between Italy and Spain that has enhanced varietal olive diversification.